The Bullwhip Effect—Impact of Stochastic Lead Time, Information Quality, and Information Sharing: A Simulation Study - Chatfield, Dean C.; Kim, Jeon G.; Harrison, Terry P.; Hayya, Jack C. (Production and Operations Management, 2004)
We use a simulation model called ‘SISCO’ to examine the effects in supply chains of stochastic lead times and of information sharing and quality of that information in a periodic order‐up‐to level inventory system. We test the accuracy of the simulation by verifying the results in Chen et al. (2000a) and Dejonckheere et al. (2004). We find that lead‐time variability exacerbates variance amplification in a supply chain, and that information sharing and information quality are highly significant. For example, using the assumptions in Chen et al. (2000a) and Dejonckheere et al. (2004), we find in a numerical experiment of a customer‐retailer‐wholesaler‐distributor‐factory supply chain that variance amplification is attenuated by nearly 50 percent at the factory due to information sharing. Other assumptions we make are based on interviews or conversations with managers at large supply chains.